Causal Determinants, Reasons, and Substantive Autonomy: a Critical Approach to Agency - Baē, Murat (Problemos, 2007)
Although the notion of agency presents itself as an attractive solution to the puzzle of free will, it faces a problem vis-ą-vis the nature of reasons that are purported to lie behind actions. In this paper, I first point out the significance of a paradigm shift that emerges with the agency view. Then I argue that the agency theories nonetheless fail in general to give a satisfactory account of various sorts of reasons underlying our actions and choices. In trying to enlighten the multi-faceted nature of actions and agency, I define a novel concept, “substantive autonomy,” and claim that it is a basic fact valid for all animals, not only humans, that are capable of initiating action. Reasons may indeed be lying behind our actions in a non-deterministic and ubiquitous manner, but agency often works in the absence of sophisticated (discursive) reasons which are evidently characteristic of humans.